Activation of STING signaling accelerates skin wound healing. Issue 1 (January 2020) - Mizutani, Yuki; Kanbe, Ayumu; Ito, Hiroyasu; Seishima, Mariko
Abstract: Background: The process of repair after skin injury is precisely regulated by a variety of mediators such as cytokines and chemokines. Recent reports demonstrated that cytoplasmic DNA-sensor cyclic GMP-AMP synthase (cGAS) activates the stimulator of interferon genes (STING) via production of cyclic GMP-AMP (cGAMP) and subsequently induces inflammatory cytokines, including type I interferon (IFN). Objective: We examined whether activation of the STING pathway by cGAMP affects the process of skin wound repair. Methods: The skin wound repair model was established using wild-type (WT) mice. Two full-thickness skin biopsies were taken from the right and left subscapular regions. One site was treated with ointment containing cGAMP, and the other was treated with a control ointment. Changes in wound size over time were calculated using photography. Results: Treatment with cGAMP significantly accelerated skin wound healing up to day 6. Biochemical analyses showed that topical treatment with cGAMP on wound sites promoted STING signaling pathway and enhanced the expression of IFN-β, CXCL10 and CCL2 in the wound sites treated with cGAMP markedly compared with the control. The scratch assay also revealed that cGAMP treatment accelerated wound closure in mouse embryonic fibroblasts. The acceleration of skin wound repair by cGAMP in WT mouse was impaired by administration of anti-IFNR antibody and anti-CXCR3 antibody respectively. Conclusion: These results revealed that topical treatment with cGAMP accelerates skin wound healing by inducing type I IFN and CXCL10/CXCR3. Topical administration of cGAMP might contribute to new effective treatments for accelerating skin wound healing.